An Overview of Neovaginal Reconstruction Options in Male to Female Transsexuals. (26th May 2014) - Bizic, Marta; Kojovic, Vladimir; Duisin, Dragana; Stanojevic, Dusan; Vujovic, Svetlana; Milosevic, Aleksandar; Korac, Gradimir; Djordjevic, Miroslav L.
Abstract : Transsexualism is a complex condition in which the person experiences the inconsistency between the desired gender and their biological gender. Absence of the vagina is devastating in male to female transsexuals. Creation of the neovagina is the main surgical problem in these patients. Historically, beginnings of the neovaginal creation have their roots in the treatment of Mayer-Rokitansky syndrome and conditions such as cloacal anomalies, certain intersex disorders, vaginal malignancies, or severe vaginal trauma, but have more recently found great purpose in male to female sex reassignment surgery. Many operative procedures have been described but none is ideal. Therefore, the search for new, improved solutions continues. In neovaginoplasty reconstruction of the vulvovaginal complex is performed in its entity. The gold standard in neovaginal reconstruction in male to female sex reassignment surgery is penile skin inversion technique with or without scrotal flaps, which enables adequate sensation of the neovagina, good neovaginal depth, good erotic sensitivity of the neclitoris, and esthetically acceptable labia minora and maiora.